Men, Machines, and Modern Times - Morison, Elting Elmore (Book collections on Project MUSE., 2017)
People have had trouble adapting to new technology ever since (perhaps) the inventor of the wheel had to explain that a wheelbarrow could carry more than a person. This text describes how we learn to live and work with innovation. It considers, among other things, the three stages of users' resistance to change: ignoring it, rational rebuttal, and name-calling.